Effect of health education intervention conducted by Primary Health Care workers on oral health knowledge and practices of nursing mothers in Lagos State - Adeniyi, Abiola Adetokunbo (J Public Health Afr, 2018)
Educational interventions on oral health care is traditionally carried out mainly by oral health workers in Nigeria. Despite the introduction of the National Oral Health Policy, oral health services/education is virtually non-existent in PHC centres in Nigeria. This study sought to determine the effect of a health education intervention delivered by Community Health Officers (CHO) on the oral health knowledge and practices of mothers attending a PHC centre in Lagos State. A pre-experimental, Before- After study design was employed. An interviewer- administered questionnaire was administered at baseline to assess the oral health care knowledge and practices of 267 mothers who enrolled in the programme. After enrolling the participants, CHO’s previously trained commenced a health education intervention on oral health. The intervention, which consisted of 2 lecture sessions, a demonstration session and a return demonstration session, utilising flipcharts and health information leaflets spanned a six-month period. Oral health knowledge and practices of participating mothers was evaluated 3 and 6 months after the intervention commenced using a standardised checklist. Data entry and analysis was done using SPSS version 20, P-value of <0.05 was considered significant. The mean oral health knowledge score at baseline was 4.58 (±1.37) while at 3-month and 6-month postintervention the mean scores were 4.68 (±0.97) and 4.96 (±0.49), respectively. There was a statistically significant increase (P=0.000) in the mean knowledge scores at 6 months post-intervention. Mothers who were 36 years or older and those with more than 12 years education displayed significantly better knowledge scores (P<0.05). Most (78.3%) reported using cotton wool or foam with water for their infants’ oral hygiene. By the second post-intervention visit, there was a significant change in the perception of the mothers on correct oral hygiene tool for infants (52.3%; P=0.000). Furthermore the percentage of mothers actually using toothbrush to clean their child’s mouth (98.1%; P=0.000) had increased. The oral health knowledge of the participants increased significantly following the intervention especially at the 6-month evaluation. PHC workers can successfully carry out oral health educational interventions at PHC level. The greatest value will occur with reinforced repetition of the messages.